Confidence and Public Speaking Anxiety among IMM Student Activists: Kepercayaan Diri dan Kecemasan Berbicara di Depan Umum di Kalangan Aktivis Mahasiswa IMM - Ulumuddin, Anastasya Apriliani Kusumaningati; Hazim, Hazim (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Public speaking is an essential skill for university students, particularly those engaged in student organizations. Specific Background: However, many students still experience anxiety when speaking in front of others, which can hinder their academic and organizational performance. Knowledge Gap: Studies that specifically investigate the relationship between self-confidence and public speaking anxiety among IMM (Ikatan Mahasiswa Muhammadiyah) activists are still limited. Aim: This study aims to examine the correlation between self-confidence and public speaking anxiety among IMM student activists at Universitas Muhammadiyah Sidoarjo. Results: Using a quantitative correlational design with 100 respondents, the findings revealed a strong negative correlation (r = -0.819) between self-confidence and public speaking anxiety, indicating that higher self-confidence is associated with lower levels of anxiety. Novelty: This study provides evidence focusing specifically on IMM activists, highlighting their psychological condition in organizational contexts. Implications: The results suggest the importance of interventions, such as public speaking training and mentoring programs, to strengthen students’ self-confidence and reduce speaking anxiety. Highlights:• Strong negative correlation between self-confidence and speaking anxiety• Focus on IMM student activists as a unique population• Practical implications for training and campus interventions Keyword: Self-Confidence, Public Speaking Anxiety, IMM Activists, Quantitative Correlation, University Students